An Observational, Prospective Survey Assessing the Control of Atrial Fibrillation in Asia Pacific: Rationale and Design of the RecordAF-AP Registry - Amerena, John; Chen, Shih-Ann; Sriratanasathavorn, Charn; Cho, Jeong-Gwan; Dejia, Huang; Omar, Razali; Fat, Tse Hung; King, Anthony (Clinical Medicine Insights. Cardiology, 2011)
Background The literature suggests that the prevalence of atrial fibrillation (AF) may be lower in Asian countries than in Western countries. Nevertheless, AF remains a significant public health problem in the region. The burden of AF, the experiences of previous trials and the lack of data on AF and its management in Asia Pacific highlight the need for a comprehensive prospective study of AF management. Methods The REgistry on Cardiac rhythm disORDers assessing the control of Atrial Fibrillation Asia Pacific (RecordAF-AP) is a prospective, observational survey of the management of recently diagnosed AF patients with 1-year follow-up in 8 countries across Asia Pacific. Eligible patients presenting with AF, treated or not, will be included in the registry and data will be recorded prospectively during follow-up visits at 6 and 12 months. Results RecordAF-AP will recruit more than 3000 patients. Study recruitment commenced in April 2009 and the final results anticipated at the end of 2011. Conclusions RecordAF-AP will assess the real-life management of AF patients in Asia Pacific, including a comparison of clinical outcomes in rhythm versus rate control strategies, providing much needed insight into the costs, treatment choices and clinical outcomes of AF patients in this region.